If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x = 3(x + -2) + 8 Reorder the terms: 5x = 3(-2 + x) + 8 5x = (-2 * 3 + x * 3) + 8 5x = (-6 + 3x) + 8 Reorder the terms: 5x = -6 + 8 + 3x Combine like terms: -6 + 8 = 2 5x = 2 + 3x Solving 5x = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5x + -3x = 2 + 3x + -3x Combine like terms: 5x + -3x = 2x 2x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 2x = 2 + 0 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 5x+8=4x+24 | | 3(x-2b)=2(x-a)-5 | | -3x+10=-30+x | | 40x-10=y | | 2k+3k=15 | | 7x-81=31+3x | | 5x^2=-30 | | y/7=-9 | | 6-2(x+3)=8 | | q-5=16 | | 2x-10=6x+30 | | 7+x+7x= | | 14m-3x= | | 25x+4y=108 | | 117=7x-2 | | 4a+2b=360 | | 6x-18=4x-3 | | 3x+12=2x+x^2 | | 5(t+7)=2(2r+7) | | 5(u+5)-2= | | -x+5=6x-2 | | -5.5x+0.57=-1.64 | | .05(x+1)-1.5=9.3 | | 2x-4+2= | | (x+3)(8)=(7)(4) | | 25x+4y=25 | | -2-5x=2x-9 | | (y+6)-2y=14 | | (3m-8)(m-8)=0 | | 5x*(x+1)=15 | | 10-2x=4x-20 | | 3xy+xyz+5x-yz-xyz-3xy= |